HySim: a tool for space-to-space hyperspectral resolved imagery - Felicetti, Leonard; Hobbs, Stephen; Leslie, Cameron; Rowling, Samuel; Dhesi, Mekhi; Harris, Toby; Brydon, George; Chermak, Lounis; Soori, Umair; Allworth, James; Balson, David (International Astronautical Federation (IAF), 2023)
This paper introduces HySim, a novel tool addressing the need for hyperspectral space-to-space imaging simulations, vital for in-orbit spacecraft inspection missions. This tool fills the gap by enabling the generation of hyperspectral space-to-space images across various scenarios, including fly-bys, inspections, rendezvous, and proximity operations. HySim combines open-source tools to handle complex scenarios, providing versatile configuration options for imaging scenarios, camera specifications, and material properties. It accurately simulates hyperspectral images of the target scene. This paper outlines HySim's features, validation against real space-borne images, and discusses its potential applications in space missions, emphasising its role in advancing space-to-space inspection and in-orbit servicing planning.
Keywords: image generation; hyperspectral imaging; multispectral imaging; space surveillance; space-to-space inspection